The Ellipsis on the Main Character's Utterances in the Trolls Movie - Diani Syahputri (English Teaching and Linguistics Journal (ETLiJ), 2020)
This study aims to: 1) identify the use of  Ellipsis   the Main Character’s Utterances in the “Trolls” Movie.,    The objectives of the study were to identify the ellipsis on the main character’s utterances in the “Trolls” movie, to determine the types of ellipsis (clausal, verbal and nominal) used on the main character’s utterances in the “Trolls” movie, and to derive the most dominant types of ellipsis found on the main character’s utterances in the “Trolls” movie. The study was conducted by applying descriptive qualitative research. The source of data was taken from the whole of “Trolls” movie and transcript of the “Trolls” movie that focused on the use ellipsis and types of ellipsis. They consisted of 38 pages as the data. The findings of the study were, there were three types of the ellipsis found in the “Trolls” movie. They were nominal ellipsis, verbal ellipsis and clausal ellipsis by the number of occurrences were nominal was 25 (39.1%), verbal ellipsis was 5 (7.8%), and clausal ellipsis was 34 (53.1%). So the most dominant type found on the main character’s utterances in the “Trolls” movie amount to 34 (53.1%).